2020
DOI: 10.1007/s00705-020-04669-5
|View full text |Cite
|
Sign up to set email alerts
|

Immune effect of a Newcastle disease virus DNA vaccine with IL-12 as a molecular adjuvant delivered by electroporation

Abstract: Newcastle disease (ND), caused by virulent Newcastle disease virus (NDV) strains, has been one of the most problematic diseases affecting the poultry industry worldwide. Conventional vaccines provide effective protection for birds to survive ND outbreaks, but they may not completely suppress NDV shedding. NDV strains circulate on farms for a long time after the initial infection and cause potential risks. A new vaccine with fast clearance ability and low viral shedding is needed. In this study, we used interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
(47 reference statements)
1
0
0
Order By: Relevance
“…Cytokines play a key role in prevention of viral infections [ 35 ]. IL-12 acts as an immunomodulator and adjuvant [ 36 ] (Peng Xie et al, 2020) and in the present study it was able to induce increased levels of CD4 + and CD8 + T cell subsets in rR2B-FPCS-CAV group, as evidenced by flow cytometry at 21, 35 and 63 days of age of the bird. IL-12 also induced IFN-γ production in this study and enhanced the CMI response as reported earlier [ 37 ].…”
Section: Discussionsupporting
confidence: 64%
“…Cytokines play a key role in prevention of viral infections [ 35 ]. IL-12 acts as an immunomodulator and adjuvant [ 36 ] (Peng Xie et al, 2020) and in the present study it was able to induce increased levels of CD4 + and CD8 + T cell subsets in rR2B-FPCS-CAV group, as evidenced by flow cytometry at 21, 35 and 63 days of age of the bird. IL-12 also induced IFN-γ production in this study and enhanced the CMI response as reported earlier [ 37 ].…”
Section: Discussionsupporting
confidence: 64%